Expectativa do consumidor de bebida funcional não alcoólica e percepção de alimentos funcionais - Menegario, Alessandra Carvalho Ferrarezi [UNESP] (2014)
This study evaluates and interprets consumer expectation of non-alcoholic functional beverage in Brazil and Portugal using the Discourse of the Collective Subject (DCS) technique. Information about the qualitative techniques most commonly used was pooled to evaluate and understand the attitude and behavior of the consumer of food and beverages, including the qualiquantitative technique the Discourse of the Collective Subject. A cross-cultural study was also performed to evaluate the consumption of non-alcoholic beverages of physical activity practitioners in Brazil and Portugal. Practitioners of physical activity from fitness centers voluntarily responded to a structured questionnaire which addressed socio-demographic data and habit of consumption of non-alcoholic beverages. This stage of the work was performed in order to identify consumers of non-alcoholic beverages and recruit individuals for subsequent interview using the DCS technique. Initially, after establishing the criteria to apply the DCS, semi-structured interviews were performed to evaluate the perception of non-alcoholic beverages consumers of functional food. To evaluate consumer expectation of non-alcoholic functional beverages, the participants were encouraged to express their expectations regarding beverage characteristics such as kind, color, flavor, texture, appearance, health benefits, and labeling information, imagining that they would develop and launch a product on the market. The DCS was evaluated according to the central ideas (CIs), key expressions (KEs) and discourse. Among the qualitative techniques used to assess consumer behavior, the DCS technique stands out by using qualitative and quantitative approach in order to evaluate the need, perception, preference, attitude and decision of consumers. The profile of physical activity practitioners in fitness centers in Brazil and Portugal was distinct. The majority of participants were 20 to 40 years old, ...